2020
DOI: 10.3389/fendo.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

ST-Segment Elevation Myocardial Infarction Related to Potential Spontaneous Coronary Thrombosis in Pheochromocytoma Crisis

Abstract: Pheochromocytoma crisis is a rare and possibly fatal emergency. Hypersecreted catecholamines may result in myocardial injury via its direct toxic effect on cardiomyocytes or mediating vasoconstriction which will reduce coronary blood flow in this special setting. Interestingly, several case studies have reported the occurrence of ST-segment elevation myocardial infarction in patients with pheochromocytoma crisis. However, no one found the angiographic evidence of occlusive thrombus in the infarct-related coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Most of these patients had patent coronary arteries; some of them had "confirmed myocardial infarction" according to the authors [44]. Anterior STEMI due to thrombus occlusion of left anterior descending artery in association with pheochromocytoma has been reported [45]. In 1954, Priest et al reported on the case of a 22-years-old farm-worker, with a "fatal myocardial infarction" [44].…”
Section: Ppgls and Acute Coronary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Most of these patients had patent coronary arteries; some of them had "confirmed myocardial infarction" according to the authors [44]. Anterior STEMI due to thrombus occlusion of left anterior descending artery in association with pheochromocytoma has been reported [45]. In 1954, Priest et al reported on the case of a 22-years-old farm-worker, with a "fatal myocardial infarction" [44].…”
Section: Ppgls and Acute Coronary Syndromementioning
confidence: 99%
“…Left ventricular thrombus, coronary thrombosis, and peripheral embolism have been reported in patients with PPGL-induced cardiac complications [13,27,37,50,87]. Chen et al reported on a case of 65-years-old male patient who in association with a PPGL-crisis developed acute anterior STEMI [45]. Coronary angiography confirmed thrombus occlusion of the left anterior descending artery.…”
Section: Ppgls and Thrombo-embolismmentioning
confidence: 99%
“…Chen et al . 7 described a case of PHEOs crisis with STEMI. In this case, the risk factors that could predispose to atherosclerosis had shown no indication of coronary plaque formation angiographically.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for CAD in pheochromocytoma is the hypercoagulability induced by pheochromocytoma leading to thrombosis in the coronary arteries. 8 Here we report an unusual case of typical MEN 2A disease in a 27-year-old female diagnosed with a left anterior descending (LAD) artery disease requiring invasive treatment.…”
Section: Introductionmentioning
confidence: 95%